Regulation of TRIF-mediated innate immune response by K27-linked polyubiquitination and deubiquitination - Xin Wu (Nature Portfolio, 2019)
TRIF is an important adaptor protein for mediating Toll-like receptor (TLR) 3 and TLR4 signaling. Here the authors show that the deubiquitinating enzymes USP19, as well as the E3 ubiquitin ligase complex Cullin-3-Rbx1-KCTD10, modulates TRIF K523 ubiquitination and thereby TRIF recruitment to TLR3/4 to control innate immunity.